TMEM106B and CPOX are genetic determinants of cerebrospinal fluid Alzheimer's disease biomarker levels. Issue 10 (14th May 2021) - Hong, Shengjun; Dobricic, Valerija; Ohlei, Olena; Bos, Isabelle; Vos, Stephanie J. B.; Prokopenko, Dmitry; Tijms, Betty M.; Andreasson, Ulf; Blennow, Kaj; Vandenberghe, Rik; Gabel, Silvy; Scheltens, Philip; et al.
Abstract: Introduction: Neurofilament light (NfL), chitinase‐3‐like protein 1 (YKL‐40), and neurogranin (Ng) are biomarkers for Alzheimer's disease (AD) to monitor axonal damage, astroglial activation, and synaptic degeneration, respectively. Methods: We performed genome‐wide association studies (GWAS) using DNA and cerebrospinal fluid (CSF) samples from the EMIF‐AD Multimodal Biomarker Discovery study for discovery, and the Alzheimer's Disease Neuroimaging Initiative study for validation analyses. GWAS were performed for all three CSF biomarkers using linear regression models adjusting for relevant covariates. Results: We identify novel genome‐wide significant associations between DNA variants in TMEM106B and CSF levels of NfL, and between CPOX and YKL‐40. We confirm previous work suggesting that YKL‐40 levels are associated with DNA variants in CHI3L1 . Discussion: Our study provides important new insights into the genetic architecture underlying interindividual variation in three AD‐related CSF biomarkers. In particular, our data shed light on the sequence of events regarding the initiation and progression of neuropathological processes relevant in AD.